Universal patterns of radio-frequency heating in nanomaterial-loaded structures. (June 2021) - Anas, Muhammad; Mustafa, Mazin M.; Vashisth, Aniruddh; Barnes, Eftihia; Saed, Mohammad A.; Moores, Lee C.; Green, Micah J.
Highlights: Nanomaterials exhibit remarkable radio frequency heating behavior. Heating can be generalized across a wide range of materials based on dielectric properties. Heating rates have a non-monotonic relationship with surface conductivity, with maximum at intermediate conductivities. This phenomena can be applied for a wide array of industrial materials processing needs. Abstract: Here we report radio frequency (RF) heating patterns that may be generalized across a wide range of nanomaterial-loaded materials. We used experiments and simulation to show that the heating rates are non-monotonically related with the conductivity of the materials. A major finding is that the maximum heating rate occurs at an optimum DC surface conductivity that is the same for thin films made using carbon nanotubes, carbon nanofibers, and laser-induced graphene. We also determine that this maximum heating is closely associated with the percolation threshold in a given structure. We show similar patterns for nano-filled thick thermoplastic parts as well. These findings can be used to optimize RF heating by tuning the bulk dielectric properties of the nanomaterial structures. Optimization of RF heating would lead to enhanced efficiency in RF-based material processing techniques being developed for automotive, aerospace, and additive manufacturing industries. Graphical abstract: Image, graphical abstract